Pengaruh Budaya K3 dan Iklim K3 Terhadap Kinerja Karyawan PT. Pelindo III (Persero) Provinsi Jawa Timur - Setiono, Benny Agus (Universitas Hang Tuah, 2018)
The purpose of this study is to examine and analyze the influence of work safety culture and work safety climate on the performance of PT. Pelindo III (Persero) East Java Province. The population in this study were all Pelindo III employees in East Java Province in the field operational field with a total of 404 people. The proportional random sampling method of sampling. Determination of the number of samples using the Slovin formula, with the number of 218 respondents. Variable measurement Safety culture is measured using indicators: management commitment, rules and procedures, communication, employee involvement, competence, work environment. Safety climate is measured by using indicators: value management, safety communication, safety practices, safety training and safety equipment. Employee performance is measured using indicators: quantity, quality, reliability, presence and ability to work together. Research Results: 1). Safety culture has a significant effect on the performance of employees of PT. Pelindo III (Persero) East Java Province. Safety culture of PT. Pelindo III (Persero) strong East Java Province will have an impact on employee performance. This is because with the application of high occupational safety employees will feel safe in carrying out work considering safety is important in the work environment. With a strong safety culture at PT. Pelindo III of East Java Province can also direct employees to behave and act, because organizations that have a strong culture have values and codes of conduct for employees to perform performance. 2). The results of safety climate have a significant effect on the performance of employees of PT. Pelindo III (Persero) East Java Province. This means that the safety climate can improve employee performance. Improved employee performance is due to the attitude of caring for the management of PT. Pelindo III East Java Province for the safety of employees and the availability of adequate safety equipment.